Quatro ou Mais Pontos de Vista sobre o Ensino de Análise Matemática - Gomes, Danilo Olímpio [UNESP]; Otero-Garcia, Sílvio César [UNESP]; Da Silva, Luciano Duarte; Baroni, Rosa Lúcia Sverzut [UNESP] (FapUNIFESP (SciELO), 2015)
This article presents results of research focused on the Analysis discipline, in Mathematics courses, with the background of a perspective of how the discipline has been structured in the Brazilian scenario, with respect to their goals, contents and bibliography. At first we saw, briefly, how course coordinators and teachers of the discipline understand the role of analysis in this major. Secondly, and constituting the main objective of this paper, we present what the undergraduates and mathematics teachers of basic education think about this discipline, through a qualitative research inspired by a phenomenological position. After the methodological procedures, three open categories were found: The presence of the analysis in the Mathematics major, The analysis as body of knowledge and The Analysis and the opening the horizon of possibilities as a teacher, which were interpreted in order to transcend the manifestations of each individual in a comprehensive synthesis movement. Finally, a third time, we present some proposals in progress and future prospects for studies about analysis education.
Four or more points of view about mathematical analysis teaching
Keywords: Mathematics Analysis Teaching; Mathematics Teacher Education; Mathematics Teaching in Undergraduate Courses